APPROACHES TO ENHANCING THE EFFECTIVENESS OF THE TRAINING AND PERSONNEL DEVELOPMENT SYSTEM IN UKRTRANSGAZ JSC STRYI PRODUCTION MANAGEMENT OF UNDERGROUND GAS STORAGE - BOIKIVSKA, Galyna; KUSHPIR, Mariana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the directions for enhancing the effectiveness of the training and personnel development system at the Ukrtransgaz JSC Stryi production management of underground gas storage. To better understand the needs and expectations of employees regarding personnel development and training, a survey of the company's managerial staff was conducted. Based on the respondents' answers, the following alternatives for training and personnel development were proposed: increasing the frequency of training sessions, incorporating more examples of real-life events, implementing international training programs and knowledge exchange with EU countries, conducting off-site training programs and involving external instructors, expanding the range of training activities, and organizing educational events. The research emphasizes the importance of training and personnel development for the successful functioning of the organization. They are identified as key elements of strategic human resource management, contributing to enhancing employee competence and supporting continuous professional growth. Improving the training and personnel development system is one of the crucial components of any enterprise's success. In today's rapidly changing world, where competition is becoming increasingly fierce and technologies are advancing every day, it is important to have a team of specialists who constantly update their knowledge and skills. The competitiveness of the enterprise and its ability to adapt to new challenges and innovations depend on this. The enterprise should undoubtedly be responsible for the training of its personnel and implement only those training forms that fully consider the needs of the workplace and individual characteristics of the staff. Additionally, it is necessary to provide motivation for employees undergoing training, so that they are interested in its successful completion and understand the benefits they will gain as a result. The enterprise should also ensure suitable conditions for training, such as adequate facilities and equipment. Furthermore, the information provided during the training process should be structured and sequential, starting from foundational stages to more complex concepts. The training process should incorporate feedback on the training outcomes, which will contribute to the further development and improvement of the personnel. Training and development tools and methods help organizations prepare their employees for new challenges, develop their potential, and ensure their ability to perform effectively. A well-structured system of training and personnel development can have a positive impact on the organization's growth, enhancing its competitiveness in the market and increasing profitability. By investing in training and development initiatives, organizations can enhance employee skills, knowledge, and abilities, enabling them to adapt to changing industry trends and technological advancements. This helps organizations stay competitive and meet the evolving needs of their customers. Various tools and methods can be utilized in training and development programs, such as workshops, seminars, online courses, mentoring, coaching, job rotations, and on-the-job training. These approaches provide employees with opportunities to acquire new knowledge, improve their job-related skills, and develop a broader understanding of the organization's goals and strategies.
Keywords: personnel training; personnel development; professional training; competencies; knowledge; motivation; strategic human capital management